A randomized controlled trial on the effectiveness of 8-week high-intensity interval exercise on intrahepatic triglycerides, visceral lipids, and health-related quality of life in diabetic obese patients with nonalcoholic fatty liver disease. Issue 12 (March 2019) - Abdelbasset, Walid Kamal; Tantawy, Sayed A.; Kamel, Dalia M.; Alqahtani, Bader A.; Soliman, Gaber S.
Abstract: Background: Medications are limited for patients with nonalcoholic fatty liver disease (NAFLD). It has been reported that aerobic exercise is effective in reducing the characteristics of NAFLD, although unclear data have ascertained the effects of high-intensity interval aerobic exercise on health-related quality of life (HRQoL) in diabetic obese patients with NAFLD. Objectives: This a randomized controlled trial aimed to ascertain the effectiveness of 8-week high-intensity interval exercise on intrahepatic triglycerides (IHTG), visceral lipids and HRQoL in diabetic obese patients with NAFLD. Study design: Between August and December 2017, 32 diabetic obese patients with NAFLD aged 45 to 60 years (21 men and 11 women) were enrolled in this study. They were randomly assigned to 2 groups, 16 patients in each group, high-intensity interval (HII) exercise and control groups. The HII group received a program of HII aerobic exercise for 8 weeks with medications of NAFLD and the control group received only medications without any type of exercise intervention. The test of IHTG, visceral lipids, and HRQoL were recorded at the initial assessment and at the end of the program after 8 weeks. Results: There were significant differences between the 2 groups at the end of the study. These study findings exhibited significant improvements in IHTG, VO2peak, visceral lipids, glycohemoglobin, plasma glucose, and all dimensions of HRQoL in the HII group ( P <.05), But there was non-significant improvement in any measure in the control group ( P >.05) after the 8-week intervention. Conclusion: Eight-week high-intensity interval aerobic exercise has a beneficial effect on IHTG, visceral lipids, and HRQoL in diabetic obese patients with NAFLD. Effort and awareness should be dedicated to encouraging the active lifestyle among different population, especially diabetic obese patients with NAFLD.